2007
DOI: 10.3354/meps331147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brown tide (Aureococcus anophagefferens) on hard clam Mercenaria mercenaria larvae and implications for benthic recruitment

Abstract: Brown tides of Aureococcus anophagefferens occur in shallow mid-Atlantic bays in the USA and attain peak summer densities of ~1000 to 2800 cells µl -1. Blooms coincide with the period of spawning and planktotrophic larval development of the hard clam Mercenaria mercenaria, a commercially important bivalve in the region. This laboratory study investigates the effects of A. anophagefferens (toxic isolate from Provasoli-Guillard Center for Culture of Marine Phytoplankton [CCMP 1708]) on hard clams throughout thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 31 publications
5
35
0
Order By: Relevance
“…HAB-forming dinoflagellates have been shown to cause mortality in multiple species of bi valve larvae, including eastern oysters Crassostrea virginica (Springer et al 2002, Leverone et al 2006, Stoecker et al 2008, Tang & Gobler 2009, northern quahogs Mercenaria mercenaria (Leverone et al 2006, Tang & Gobler 2009, bay scallops Argopecten irradians irradians and A. i. concentricus (Springer et al 2002, Yan et al 2003, Leverone et al 2006, Tang & Gobler 2009, and Japanese scallops Chlamys farreri (Yan et al 2001). In addition, the brown tide-forming pelagophyte Aureococcus ano pha gefferens has been shown to reduce survival, growth, and lipid content of northern quahog larvae (Padilla et al 2006, Bricelj & MacQuarrie 2007 and can slow the growth of larval bay scallops (Gallager et al 1989).Elevated concentrations of carbon dioxide (CO 2 ) are also a significant threat to coastal bivalve populations. CO 2 levels have risen by 40% since the industrial revolution (Caldeira & Wickett 2003), and the rate of increase has tripled since the mid-20th century (Fussel 2009, Friedlingstein et al 2010.…”
mentioning
confidence: 99%
“…HAB-forming dinoflagellates have been shown to cause mortality in multiple species of bi valve larvae, including eastern oysters Crassostrea virginica (Springer et al 2002, Leverone et al 2006, Stoecker et al 2008, Tang & Gobler 2009, northern quahogs Mercenaria mercenaria (Leverone et al 2006, Tang & Gobler 2009, bay scallops Argopecten irradians irradians and A. i. concentricus (Springer et al 2002, Yan et al 2003, Leverone et al 2006, Tang & Gobler 2009, and Japanese scallops Chlamys farreri (Yan et al 2001). In addition, the brown tide-forming pelagophyte Aureococcus ano pha gefferens has been shown to reduce survival, growth, and lipid content of northern quahog larvae (Padilla et al 2006, Bricelj & MacQuarrie 2007 and can slow the growth of larval bay scallops (Gallager et al 1989).Elevated concentrations of carbon dioxide (CO 2 ) are also a significant threat to coastal bivalve populations. CO 2 levels have risen by 40% since the industrial revolution (Caldeira & Wickett 2003), and the rate of increase has tripled since the mid-20th century (Fussel 2009, Friedlingstein et al 2010.…”
mentioning
confidence: 99%
“…On the other hand, in adult suspensionfeeding bivalves, Aureococcus can inhibit the activity of lateral cilia in the gill (Gainey and Shumway 1991), thereby reducing their growth (Bricelj 1999). In BB-LEH, the reduced growth in juvenile clams has been reported in association with high density of brown tide (Bricelj and MacQuarrie 2007). Studies show that 35% of the state's SAV (submerged aquatic vegetation) habitat in BB-LEH is at significant risk of negative impacts due to brown tide blooms (Gastrich et al 2004).…”
Section: Brown Tide Aureococcus Anophagefferensmentioning
confidence: 99%
“…More recently, Heterocapsa circularisquama has been shown to reduce activity rate and swimming velocity of spermatozoa of Japanese pearl oyster, Pinctada fucata martensi (Basti et al 2013). Several studies have also reported recruitment failure of various bivalve species following HABs (Granmo et al 1988;Summerson and Peterson 1990;Leverone et al 2006;Bricelj and MacQuarrie 2007;Tang and Gobler 2009), suggesting a potential impact on gamete quality. Indeed, reproductive output and success is at least partially dependent on gamete quality, as it can influence fertilization, embryogenesis and larval development in free-spawning shellfish (Lewis and Ford 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of sperm cellular characteristics in cultivated and "exploited" areas could serve as a complementary tool for predicting reduced or unsuccessful recruitment sometimes observed in the field (Granmo et al 1988;Summerson and Peterson 1990;Leverone et al 2006;Bricelj and MacQuarrie 2007;Tang and Gobler 2009).…”
Section: Introductionmentioning
confidence: 99%